2018
DOI: 10.3389/fenvs.2018.00012
|View full text |Cite
|
Sign up to set email alerts
|

Post-Emergence Herbicidal Activity of Nanoatrazine Against Susceptible Weeds

Abstract: Poly(ε-caprolactone) (PCL) nanocapsules have been previously developed as a carrier system for atrazine. However, the efficacy of this nanoformulation against weeds commonly found in crop cultures has not been tested yet. Here, we evaluated the post-emergence herbicidal activity of PCL nanocapsules containing atrazine against Amaranthus viridis (slender amaranth) and Bidens pilosa (hairy beggarticks), in comparison with a commercial formulation of atrazine. For both species, treatment with atrazine-loaded nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…In contrast, the tenfold dilution of non‐nanoatrazine compromised its pre‐emergence herbicidal activity. Similar results have been reported for the same nanoatrazine and non‐nanoformulation in the post‐emergence control of B. juncea , B. pilosa and A. viridis , suggesting that atrazine nanoencapsulation potentiates both its pre‐ and post‐emergence herbicidal activity . Thus, nanoencapsulation would allow a reduction in applied atrazine levels, maintaining satisfactory weed control concomitant with reduced environmental contamination.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In contrast, the tenfold dilution of non‐nanoatrazine compromised its pre‐emergence herbicidal activity. Similar results have been reported for the same nanoatrazine and non‐nanoformulation in the post‐emergence control of B. juncea , B. pilosa and A. viridis , suggesting that atrazine nanoencapsulation potentiates both its pre‐ and post‐emergence herbicidal activity . Thus, nanoencapsulation would allow a reduction in applied atrazine levels, maintaining satisfactory weed control concomitant with reduced environmental contamination.…”
Section: Discussionsupporting
confidence: 81%
“…For example, the high sand percentage and low organic matter content of the soil used in the present study are probably related to the intense residual effect detected here, as the low atrazine sorption to soil organic and inorganic particles increases the herbicide availability to the plants . Although the current results, together with previous studies of our group, have shown satisfactory control of different plant species by nanoatrazine, field experiments with mixed weed populations are essential to verify the efficacy of this nanoformulation under realistic conditions . Further studies are also needed to elucidate the possible toxic effects of these nanocapsules to non‐target organisms, such as the soil microbiota.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations